Rights of self-delimiting peoples: protecting those who want no part of us - Miller, Lantz Fleming (Human rights review, 2013)
While in recent years new charters and government actions have boosted the collective and individual rights enjoyed by “Fourth-World” indigenous peoples such as the Inuit, another set of indigenous peoples has not experienced such protection: “self-delimiting” peoples. Their rights go largely unprotected because of deliberate ambiguities in the word “indigenous”; because these peoples generally avoid all contact with the larger society, and so are unknown by it and have no voice in it; and because charters and institutions generally require validation of an indigenous people as bona fide—such as a history of contact and of evident land occupation—in order for the group to enjoy full rights protections. Both practice and theory may militate against the extension of full protection. This paper argues that theory, institutions building upon it, and practice realizable from theory and institutions must be reconsidered in terms of the particular circumstances and needs of these peoples if their rights are to be fully respected and maintained. Clear, special protection for these peoples’ rights to their culture must be established.